Stereotactic body radiation therapy for early-stage non–small-cell lung cancer in octogenarians and older: an alternative treatment. (8th May 2020) - Bei, Yanping; Murakami, Naoya; Nakayama, Yuko; Okuma, Kae; Kashihara, Tairo; Raturi, Vijay Parshuram; Okamoto, Hiroyuki; Takahashi, Kana; Inaba, Koji; Igaki, Hiroshi; Itami, Jun
ABSTRACT: Surgery is the standard modality for early-stage I–II non-small-cell lung cancer (NSCLC). Generally, patients who are >80 years old tend to have more comorbidities and inferior physical status than younger patients. Stereotactic body radiation therapy (SBRT) may provide an alternative treatment for this group of patients. Here, we report our experience using SBRT to in the management of early-stage NSCLC in patients >80 years old. Patients aged ≥80 years old who were diagnosed with early-stage NSCLC and treated with definitive lung SBRT from January 2000 to January 2018 were retrospectively analysed. Local recurrence-free survival (LRFS), regional recurrence-free survival (RRFS), cancer-specific survival (CSS), progression-free survival (PFS), overall survival (OS) and treatment-related toxicities were analysed for patients >80 years old. A total of 153 patients were included, with a median age of 85 years (range, 80–94). The median follow-up period and OS was 39.8 months (range, 10–101 months) and 76 months, respectively. The 3-year OS, PFS, CSS, RRFS and LRFS were 65.3, 58.0, 75.7, 73.9 and 85.3%, respectively. Radiation pneumonitis grade 0–1, grade 2, grade 3 and grade 4 was observed in 135 (88.2%), 13 (8.5%), 4 (2.61%) and 1 (0.6%) patient(s), respectively. On multivariate analyses, tumor size, pretreatment C-reactive protein (CRP) value, histology and pretreatment physical state were significantly associated with OS. Definitive lung SBRT appears to have high LRFS and OS without causing high-grade radiation-related toxicities in early-stage NSCLC patients who were >80 years old.